133 Influence of Particle Size of Enogen Feed Corn and Conventional Yellow Dent Corn on Nursery and Finishing Pig Performance, Carcass Characteristics and Stomach Morphology. (7th May 2021) - Williams, Hadley; Tokach, Mike D; Woodworth, Jason C; Goodband, Robert D; DeRouchey, Joel M; Dritz, Steve S; Wecker, Haley; Calderon, Hilda I
Abstract: Two studies evaluated the effect of particle size of Enogen® Feed corn (Syngenta Seeds, LLC, Downers Grove, IL) and conventional yellow dent corn on nursery and finishing pig performance, carcass characteristics and stomach morphology. In Exp. 1, 360 nursery pigs (DNA 200×400, Columbus, NE; initially 6.6±0.1 kg BW) were used with 5 pigs per pen and 12 pens per treatment. Treatments were arranged in a 2×3 factorial with main effects of corn source (Enogen Feed corn or conventional yellow dent corn) and ground corn particle size (300, 600, or 900 µm). Overall, there was a corn source×particle size interaction (linear, P = 0.027) for G:F ratio. There was no difference due to particle size when pigs were fed conventional yellow dent corn, but in pigs fed Enogen Feed corn, G:F increased with decreasing particle size. Neither corn source nor particle size affected (P > 0.05) ADG or ADFI. In Exp. 2, 323 finishing pigs (241′600; DNA, Columbus, NE; initially 50.0±1.3 kg) were used with 8 or 9 pigs per pen and 6 pens per treatment. Treatments were arranged identical to Exp. 1. Overall, corn source did not elicit differences in ADG, ADFI or G:F (P > 0.05). For corn particle size, ADG and G:F increased (linear, P ≤ 0.014) and ADFI decreased (P = 0.043) as particle size decreased. For carcass characteristics, there was a tendency (linear, P = 0.093) for increased HCW and increased (linear, P = 0.023) carcass yield as corn particle size decreased. For stomach morphology, there was a tendency for a corn source×particle size interaction (P = 0.055) for keratinization score with keratinization increasing linearly (P = 0.001) as particle size decreased for yellow dent corn with no change in keratinization score as particle size decreased for Enogen Feed corn. In summary, reducing corn particle size improved G:F with no major differences observed between corn sources for overall pig performance.